An investigation of effect of hematocrit on thermal conductivity of a bio-nanofluid (MWCNT or SWCNT with blood). (1st October 2021) - Ali, Ali J.; Eddin, Bahaa E.; Chaichan, Miqdam T.
Graphical abstract: Highlights: Theoretical models used to study the hematocrit difference effect on the thermal conductivity of bio-nanofluids. Two types of carbon nanotubes (MWCNTs or SWCNTs) were added to blood. Age and gender variations cause noticeable differences in the thermal conductivity of biofluid. When treating cancer by cells' heating, the amount of nanoparticles added must be taken into account. Abstract: Nanotechnology has entered many fields, such as cancer treatment, biomedical imaging, and other applications. Bio-nanofluid (blood with nanoparticles) could play a greater role in the future in diseases and epidemics. This study investigates the effect of the hematocrit thermal conductivity (TC) difference when two types of carbon nanotubes (MWCNTs and SWCNTs) are added to blood to form bio-nanofluid using theoretical models. Previous studies did not take into account the difference in hematocrit. The mathematical models used to calculate TC of the bio-nanofluid (blood with nanoparticles) were selected according to the data available in the literature and are taken according to the shape of the added nanoparticles. This study evaluates the effect of volumetric fraction of red blood cells (hematocrit) in blood according to age and gender on the effective thermal conductivity of the bio-nanofluid used in the treatment of tumors by hyperthermia was studied. In order to conduct the study, Yang's model was used to calculate the thermal conductivity of the nanofluid consisting of plasma-CNT and the Maxwell model to calculate the thermal conductivity of the final bio-nanofluid (plasma-CNT + red blood cells). The selected and used volumetric fraction for both nanomaterials was 0.03%. The results showed that there are differences in the thermal conductivity of the bio-nanofluid with the change of the hematocrit value, which depends on gender (men or women) and age (children or adults). Using SWCTs (0.7 nm size) resulted in K(bio-nanofluid) in men to be higher by 2.1% and 4.24% than women and children, respectively. Meanwhile, K(bio-nanofluid) values increased for men compared to women and children by 1.49% and 3%, respectively, by using MWCNTs with a radius (2 nm size).